Less is more: A systematic review and meta-analysis of the outcomes of radical versus conservative primary resection in anorectal melanoma. (August 2020) - Smith, Henry G.; Glen, Jessica; Turnbull, Nancy; Peach, Howard; Board, Ruth; Payne, Miranda; Gore, Martin; Nugent, Karen; Smith, Myles J.F.
Abstract: Introduction: Anorectal melanoma (ARM) is a rare disease with a poor prognosis. There is no consensus as to the optimal primary surgical treatment for ARM, with advocates for both radical (abdominoperineal resection [APR]) and conservative strategies (wide local excision [WLE]). Here, we report a systematic review of studies comparing outcomes between these strategies. Methods: Studies comparing APR with WLE in patients with ARM were included, and a systematic review using the Grading of Recommendations, Assessment, Development and Evaluation methodology was performed. Outcomes deemed critical included overall survival, disease-free survival, local recurrence and quality of life. Results: Forty studies were identified, of which 27 were suitable for inclusion. Twenty-three studies compared overall survival between WLE and APR, with no difference in outcomes noted (risk ratio [RR]: 0.80, 95% confidence interval [CI]: 0.60–1.07, p = 0.13). Seven studies compared disease-free survival, with no difference in outcomes noted (RR: 1.08, 95% CI: 0.61–1.91, p = 0.79). A total of 19 studies compared local recurrence rates, with again no significant difference in outcomes noted (RR: 0.71, 95% CI: 0.44–1.14, p = 0.16). None of the studies identified reported quality of life–related outcomes. Conclusion: There is no evidence to suggest that a radical primary surgical strategy improves outcomes in ARM. Therefore, given the well-documented morbidity associated with APR, WLE with regular surveillance for local recurrence should be the primary strategy in most patients. Highlights: Anorectal mucosal melanomas (ARM) are rare malignancies with poor patient outcomes. The optimal primary surgical strategy is yet to be defined, with advocates for both radical and conservative resections. This meta-analysis did not find an oncological benefit for radical resection over conservative resection. Therefore we argue that conservative resection should be the default approach for primary ARM.